Synthesis of Chlorosubstituted 3,5-Diaryl-1-substituted Pyrazolines in - Deshmukh, P.N.; Jamode, V.S. (Asian Journal of Chemistry, 2010)
Pyrazoline derivatives have been extensively studied because of their ready accessibility through synthesis, diverse chemical reactivity, various biological activities and variety of industrial applications. New chlorosubstituted 3,5-diaryl-1-substituted pyrazolines (3a-i), (4a-i) and (5a-i), were synthesized from 1,3-diaryl-prop-2-ene-1-ones (2a-i) on condensation with nucleophiles like thiosemicarbazide, isonicotinicacidhydrazide and semicarbazide hydrochloride in ethanol/DMFmedium. The synthesized compounds have been characterized by IR and 1H NMR spectroscopic studies.